Cesarean in the Second Stage: A Possible Risk Factor for Spontaneous Preterm Birth. Issue 1 (March 2018) - Berghella, V.; Gimovsky, A.C.; Levine, L.D.; Vink, J.
Abstract : This brief editorial addressed the findings of Wood et al of an increased risk of spontaneous preterm birth (SPTB) in women with a prior cesarean delivery (CD) in the second stage of labor compared with women with a prior spontaneous vaginal delivery, as well as related literature. Wood et al found that prior second-stage CD had an odds ratio of 2.44 (95% confidence interval, 1.91-3.10) for the risk of subsequent SPTB <32 weeks, after adjusting for confounders such as maternal age, smoking, and maternal weight. Even after controlling for route of delivery, Wood et al found no significant association between the length of the second stage (even >3 or >4 h) and subsequent SPTB, results that suggested that CD in the second stage of labor, and not the duration of the second stage, was associated with SPTB.